CHRISTIAN PHILOSOPHICAL REFLECTION ON REBIRTH: BRING THIS DISCUSSION INTO OUR CLASSROOM - Ezra Anantawikrama; Samuel Soegiarto (Aletheia Christian Educators Journal, 2023)
There are only three major competing theories regarding life after death. Atheism holds the theory that life ends at one’s death. Another theory is the reincarnation view held by most people on this planet. Rebirth is often grouped as part of the reincarnation view. The last theory, held by Judeo-Christian and Islam religions, is the resurrection, often called the heaven and hell view. Proponents of each theory attack other theories, and debates have become common in social media, often confusing students. There is a significant need for Christian educators to equip themselves before preparing students to learn comparative religions. Teachers must be well-versed in answering objections to the Christian faith. This paper helps teachers understand the reincarnation theory, emphasizing the rebirth view and showing why the theory is attractive. It then gives philosophical responses based on the Christian worldview. The paper concludes with two short pieces of advice for Christian educators.